Annealing effect on the thermal conductivity of thermoelectric ZnTe nanowires - Shaygan, Mehrdad; Kheirabi, Nazli; Davami, Keivan; Mortazavi, Bohayra; Lee, Jeong-Soo; Cuniberti, Gianaurelio (Giovanni); Meyyappan, M. (Materials Letters, 2014)
We report here the effect of thermal annealing on the thermal conductivity of ZnTe nanowires measured on a microfabricated suspended device. Molecular dynamics simulation was used to calculate the effect of contacts on the measurements at different temperatures and to estimate the intrinsic nanowire thermal conductivity values. A decrease in thermal conductivity was observed after each thermal annealing step at all the measured temperatures. Thermal annealing can be a potential method to improve the thermoelectric efficiency of nanowires, not only by enhancing the electrical conduction as demonstrated before, but also by suppressing the thermal transport at the same time. © 2014 Elsevier B.V.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Nanowire; Thermal conductivity; Thermoelectric; ZnTe